Development of XFCT imaging strategy for monitoring the spatial distribution of platinum‐based chemodrugs: Instrumentation and phantom validation. Issue 3 (13th February 2013) - Kuang, Yu; Pratx, Guillem; Bazalova, Magdalena; Qian, Jianguo; Meng, Bowen; Xing, Lei
Abstract : Purpose: : Developing an imaging method to directly monitor the spatial distribution of platinum‐based (Pt) drugs at the tumor region is of critical importance for early assessment of treatment efficacy and personalized treatment. In this study, the authors investigated the feasibility of imaging platinum (Pt)‐based drug distribution using x‐ray fluorescence (XRF, a.k.a. characteristic x ray) CT (XFCT). Methods: : A 5‐mm‐diameter pencil beam produced by a polychromatic x‐ray source equipped with a tungsten anode was used to stimulate emission of XRF photons from Pt drug embedded within a water phantom. The phantom was translated and rotated relative to the stationary pencil beam in a first‐generation CT geometry. The x‐ray energy spectrum was collected for 18 s at each position using a cadmium telluride detector. The spectra were then used for the K‐shell XRF peak isolation and sinogram generation for Pt. The distribution and concentration of Pt were reconstructed with an iterative maximum likelihood expectation maximization algorithm. The capability of XFCT to multiplexed imaging of Pt, gadolinium (Gd), and iodine (I) within a water phantom was also investigated. Results: : Measured XRF spectrum showed a sharp peak characteristic of Pt with a narrow full‐width at half‐maximum (FWHM) (FWHMKα1 = 1.138 keV, FWHMKα2 = 1.052 keV). The distribution of Pt drug in the water phantom was clearly identifiable on the reconstructed XRF images. Our results showed a linear relationship between the XRF intensity of Pt and its concentrations ( R 2 = 0.995), suggesting that XFCT is capable of quantitative imaging. A transmission CT image was also obtained to show the potential of the approach for providing attenuation correction and morphological information. Finally, the distribution of Pt, Gd, and I in the water phantom was clearly identifiable in the reconstructed images from XFCT multiplexed imaging. Conclusions: : XFCT is a promising modality for monitoring the spatial distribution of Pt drugs. The technique may be useful in tailoring tumor treatment regimen in the future.